Strategic guidelines for the development of marinas in the segment of mega-yachts in The Republic of Croatia - Škorić, Saša; Favro, Srećko; Šerić, Neven (Turizam, 2018)
Nautical tourism is specific because it depends on maritime and coastal region, natural geographical prerequisites, specific infrastructure and many other specific environment factors. It consists of three segments, Charter tourism, Cruise trips and Marinas. Mega-yachts as subsegment of segment Marinas is very specific with high financial value in comparison with other elements of nautical tourism, but it is unattended in comparison to the other ones. The least represented subsegment of segment Marinas in the Republic of Croatia is Mega-yachts berths that should provide the greatest possibilities in terms of profit. It is necessary to adjust present situation and carry out analysis that will result with guidelines defining strategically aims of marinas for the berthing of mega-yachts in Croatia, following the trends of nautical tourism.   There are not enough real data regarding future needs for mega-yachts berths in realized studies and made strategic guidelines. The aim of this research is making of strategic guidelines those can provide further growth and development of marinas in subsegment of mega-yachts, but it could also be a good backup for lot of other activities those are necessary for that segment of nautical tourism. It should assure their whole year residence in Croatia that would bring the economic development of marinas and it would speed up development of accompanying services, too. Five determined hypothesis have been tested and confirmed in this work. Two standard research methods were used. Secondary data were collected by research method round the table, while primary data were collected by query on Croatian and English language, with personal interviews and observations. The results from this research have shown that Croatia has the potential to attract the mega-yachts, offering various services and development of services for attracting the mega-yachts and extend the tourist season. All of the above-mentioned contributes to the hiring of the population, attracting the investments, increasing the economic standard and local community development.